Letter to the proprietors of East India Stock, in behalf of the present owners of East India Shipping, by a proprietor (Debrett, 1795)
In: Jackson, Randle. The Substance of a speech delivered at the East India House, on [...] January 21, 1795, in support of a restriction [resolution] of the honourable the Court of Directors for Conducting the Shipping of the East-India Company in future, upon principles of fair and open competition.